Modeling of Transverse Thermal Cracking of FRP Bars Embedded in Concrete - Xu, Tao; Zhao, Gaofeng; Tang, Chun-an; Ranjith, P. G. (Arabian Journal for Science and Engineering, 2014)
A thermo-mechanical model is employed to analyze the thermo-mechanical behavior of a widely used Fiber reinforced polymer reinforced concrete subject to thermo-mechanical loading under service conditions. The governing equations including heat transfer, thermo-mechanical deformation and damage evolution are briefly described in the model. A numerical model of glass fiber reinforced polymers (GFRP) embedded in concrete is then proposed to investigate thermally-induced damage and crack propagation at elevated temperatures. Numerical results are presented and compared with experimental and theoretical results in the form of crack propagation in stress profiles. The numerical simulations show that the crack propagation behavior of the GFRPembedded in concrete is closely dependent on the physico-mechanical properties of GFRP and concrete. The numerical study reveals that the cracking developed at the interface between the GFRP bar and the concrete was due to the significant difference in thermal expansion properties between the concrete and the GFRP at elevated temperatures. The numerical study also demonstrates that the model proposed can visually replicate the thermal cracking propagation process of concrete cover and provide good estimates of the critical temperature increment of concrete cover failure of a circular concrete reinforced with a single GFRP bar.